MITOCHONDRIAL DNA DIVERSITY IN FOUR POPULATIONS OF INDONESIAN FRESHWATER GIANT PRAWN (Macrobrachium rosenbergii) - Ratu Siti Aliah; Sutanti; Fetrilisa Silitonga (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Mitochondrial DNA has been widely applied to analyze fish genetic diversity, especially the cytochrome oxidase subunit I (COI) gene, which can be used as a marker of typical variation patterns, both intraspecific and interspecific crossbreeding. Haplotype diversity was observed in four populations of giant freshwater prawns (Macrobrachium rosenbergii) originating from Peureulak River in Aceh, Tabuk River in South Kalimantan, Bengawan Solo River in East Java, and the Siratu strain. Haplotype diversity was observed in the mitochondrial DNA COI gene of 1516 bp and restricted using 5 enzymes, namely AvaII, MspI, RsaI, HaeIII, and TaqI. The diversity of mtDNA COI haplotypes in the population of Peureulak River, Tabuk River, Bengawan Solo River, and Siratu were 0.8183, 0.6222, 0.7461, and 0.8044, respectively. The dendrogram of genetic distance showed that the Bengawan Solo River populations and the Siratu strain were in the same cluster, while Peureulak River and Tabuk River populations were in another group. The four populations can be used as genetic sources in crossbreeding activities based on haplotype data for each population, haplotype diversity, and genetic distance. DNA Mitokondria telah banyak diaplikasikan untuk analisa keragaman genetik ikan, terutama gen cytochrome oxidase subunit I (COI) yang dapat digunakan sebagai penanda pola variasi yang khas baik pada persilangan intraspesifik maupun interspesifik. Keragaman haplotipe diamati pada empat populasi udang galah (Macrobrachium rosenbergii) yang berasal dari Sungai Peureulak di Aceh, Sungai Tabuk di Kalimantan Selatan, Sungai Bengawan Solo di Jawa Timur dan strain Siratu. Keragaman haplotipe diamati pada gen COI DNA mitokondria yang berukuran 1516 bp dan direstriksi menggunakan 5 enzim, yaitu AvaII, MspI, RsaI, HaeIII, dan TaqI. Keragaman haplotipe mtDNA COI pada populasi Sungai Peureulak, Sungai Tabuk, Sungai Bengawan Solo dan Siratu masing-masing adalah 0,8183; 0,6222; 0,7461 dan 0,8044. Dendrogram jarak genetik menunjukkan bahwa populasi Sungai Bengawan Solo dan galur Siratu berada dalam 1 kluster yang sama, sedangkan populasi Sungai Peureulak dan Sungai Tabuk berada pada kluster lainnya. Berdasarkan data haplotipe untuk setiap populasi, keragaman haplotipe dan jarak genetik keempat populasi tersebut dapat dijadikan sebagai sumber genetik dalam kegiatan persilangan.